Embedded solar adaptive optics telescope: achieving compact integration for high-efficiency solar observations - Naiting Gu; Hao Chen; Ao Tang; Xinlong Fan; Carlos Quintero Noda; Yawei Xiao; Libo Zhong; Xiaosong Wu; Zhenyu Zhang; Yanrong Yang; Zao Yi; Xiaohu Wu; et al. (Opto-Electronic Advances)
Adaptive optics (AO) has significantly advanced high-resolution solar observations by mitigating atmospheric turbulence. However, traditional post-focal AO systems suffer from external configurations that introduce excessive optical surfaces, reduced light throughput, and instrumental polarization. To address these limitations, we propose an embedded solar adaptive optics telescope (ESAOT) that intrinsically incorporates the solar AO (SAO) subsystem within the telescope's optical train, featuring a co-designed correction chain with a single Hartmann-Shack full-wavefront sensor (HS f-WFS) and a deformable secondary mirror (DSM). The HS f-WFS uses temporal-spatial hybrid sampling technique to simultaneously resolve tip-tilt and high-order aberrations, while the DSM performs real-time compensation through adaptive modal optimization. This unified architecture achieves symmetrical polarization suppression and high system throughput by minimizing optical surfaces. A 600 mm ESAOT prototype incorporating a 12×12 micro-lens array HS f-WFS and 61-actuator piezoelectric DSM has been developed and successfully conducted on-sky photospheric observations. Validations including turbulence simulations, optical bench testing, and practical observations at the Lijiang observatory collectively confirm the system's capability to maintain about λ/10 wavefront error during active region tracking. This architectural breakthrough of the ESAOT addresses long-standing SAO integration challenges in solar astronomy and provides scalability analyses confirming direct applicability to the existing and future large solar observation facilities.